2013
DOI: 10.1021/jp403031p
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Indium Carbide Cluster Ions: Experimental and Computational Study

Abstract: We report the observation and structural analysis of novel indium carbide gas phase cluster ions generated by bombardment of a clean indium surface by keV C60(–) ions. Positive In(m)C(n)(+) (m = 1–21, 1 ≤ n ≤ 9) ions were ejected off the surface and analyzed mass spectrometrically. C60(–) ion beam irradiation is shown to be an efficient way of producing new kinds of gas phase carbide ions with relatively balanced stoichiometries. The rise kinetics of the ion signal (immediate jump within the beam opening time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…The additional formation of CO 2 at higher temperatures (peak maximum at 300 °C) compared to Ce–ZrO 2 only might be assigned to the reduction of surface In 2 O 3 . Reduction is not expected to lead to the formation of In-carbides under the employed conditions . Besides, CH 4 is also formed and accompanied by the formation of CO 2 in the whole temperature range, indicating that the catalyst is also active for CO 2 hydrogenation to CH 4 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The additional formation of CO 2 at higher temperatures (peak maximum at 300 °C) compared to Ce–ZrO 2 only might be assigned to the reduction of surface In 2 O 3 . Reduction is not expected to lead to the formation of In-carbides under the employed conditions . Besides, CH 4 is also formed and accompanied by the formation of CO 2 in the whole temperature range, indicating that the catalyst is also active for CO 2 hydrogenation to CH 4 .…”
Section: Resultsmentioning
confidence: 93%
“…29 Reduction is not expected to lead to the formation of In-carbides under the employed conditions. 43 Besides, CH 4 is also formed and accompanied by the formation of CO 2 in the whole temperature range, indicating that the catalyst is also active for CO 2 hydrogenation to CH 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Two kinds of products were identified: The precipitate, which was composed of Ga particles coated with C‐dots, and the supernatant, in which Ga‐doped C‐dots (Ga@ C‐dots) were obtained . When gallium was sonicated in n ‐hexane or n ‐heptane, Raman spectroscopy revealed that the Ga spheres were coated with a carbon film . In the present work, we further investigate the products of sonication of molten gallium in organic liquids (decane, dodecane, and hexadecane) and focus on the effect of the sonication conditions (duration and intensity) on the nature of these products.…”
Section: Introductionmentioning
confidence: 99%
“…Bernstein et al. reported the formation of indium carbide gas‐phase cluster ions generated by the bombardment of a clean indium surface by 14 keV C60 ions …”
Section: Introductionmentioning
confidence: 99%
“…The great majority of the MC's studied to date have been cluster-type structures involving transition metals. [1][2][3][4] Transition metal carbides (TMC's) especially have received considerable attention and are being investigated for applications in areas such as catalysis in chemicals production and fuel cell design. [5][6][7] Whilst TMC's have been the subject of study for a number of decades, in recent years interest has begun to turn towards the later p-block metallic elements.…”
Section: Introductionmentioning
confidence: 99%